Clinical Profile of Pericardial Effusion in Adult Patients - Katwal, Sushant; Nepal, Rajesh; Budhathoki, Sampanna; Yadav, Manoj Kumar; Acharya, Pritha (Journal of Nobel Medical College, 2026)
Background: Pericardial effusion is an abnormal collection of fluid in the pericardial cavity, the main causes of which are idiopathic, neoplastic, autoimmune and infective. It can present incidentally or with life threatening tamponade physiology. The timely identification and management are paramount in improving patients’ outcome. Materials and Methods: A cross-sectional study was conducted in adult patients with moderate and large pericardial effusion with or without tamponade or mild effusion with cardiac tamponade. Clinical history, examination, laboratory investigations, echocardiographic findings, and pericardial fluid analyses were evaluated in 56 patients. The etiology was determined based on microbiological, cytological, biochemical and histopathological criteria. Results: The mean age of the participants was 52.9 years. Shortness of breath (76.8%), cough (75%), and chest pain (71.4%) were the most common presentation. Mild, moderate and large pericardial effusions were noted in 3.6%, 58.9% and 37.5% of the participants respectively; whereas 51.8% of the patients had cardiac tamponade. The most common etiology was idiopathic (42.9%), tuberculosis (16.1%), and malignancy (14.3%). Hemorrhagic effusions correlated with malignancy (p = 0.008) and the presence of fibrin stands on echocardiography were noted in tubercular effusion (p<0.001). Conclusion: Idiopathic pericardial effusion was the most frequent cause, although tuberculosis and malignancy remain significant contributors in eastern Nepal. Fibrin strands on echocardiography and hemorrhagic pericardial fluid on pericardiocentesis are valuable diagnostic clues suggestive of tuberculosis and malignancy, respectively.